(untitled) (Romanian Biotechnological Letters, 2025)
Algae biotechnology is an emerging discipline that explores the potential of these marine plants in industrial, environmental, and food applications. Thanks to their rapid growth, high productivity, and richness in bioactive compounds, algae have become a sustainable source for obtaining materials of scientific interest. Algal biomaterials are used in various thanks to their natural, renewable, and biodegradable properties. The first part of this state-of-the-art review addressed marine polysaccharides, which have a complex molecular architecture whose composition defines their physicochemical and biological properties. The second part addressed sulfated polysaccharides, their types, extraction, and main applications. Finally, biosilica was discussed as an algal mineral with unique nanopores and morphologies, useful as an adsorbent and catalytic support. The application of these algal biomaterials encompasses tissue engineering, controlled drug delivery, food, cosmetics, water treatment, and environmental remediation.